Intensity of Glycemic Exposure in Early Adulthood and Target Organ Damage in Middle Age: The CARDIA Study - Lin, Yifen; Zhong, Xiangbin; Xiong, Zhenyu; Zhang, Shaozhao; Liu, Menghui; Fan, Yongqiang; Huang, Yiquan; Sun, Xiuting; Zhou, Huimin; Xu, Xingfeng; Guo, Yue; Li, Yuqi; et al. (Frontiers in Physiology, 2021)
Aim: To determine whether long-term intensity of glycemic exposure (IGE) during young adulthood is associated with multiple target organs function at midlife independent of single fasting glucose (FG) measurement. Methods: We included 2,859 participants, aged 18-30 years at Y0, in the Coronary Artery Risk Development in Young Adults (CARDIA) Study. IGE was calculated as the sum of (average FG of two consecutive examinations × years between the examinations) over 25 years. Target organs function was indicated by cardiac structure, left ventricular (LV) systolic function, LV diastolic function, coronary artery calcium (CAC) and urine albumin-to-creatinine ratio (UACR) at Y25. We evaluated the associations between IGE with target organs function using linear regression models and estimated the associations between IGE with numbers of organs involved (0, 1, or ≥2 organs) using multinomial logistic regression models. Results: A 1-SD increment of IGE was significantly associated with worse target organs function after multivariable adjustment: left ventricular mass (β [SE], 5.468 [1.175]); global longitudinal strain (β [SE], 0.161 [0.071]); E/e’ ratio (β[SE], 0.192 [0.071]); CAC score (β [SE], 27.948 [6.116]) and log UACR (β [SE], 0.076 [0.010]). Besides, IGE was independently associated with having ≥2 organs involved in both overall population (OR [95% CI], 1.48 [1.23, 1.41], p<0.001) and subgroups stratified by diabetes at Y25. Conclusion: Higher intensity of glycemic exposure during young adulthood was independently associated with subclinical alterations of target organs function at midlife. Our findings highlight the importance of early screening and management of IGE in youth.